Coagulation factors in the airways in moderate and severe asthma and the effect of inhaled steroids. Issue 12 (23rd August 2009) - Brims, F J H; Chauhan, A J; Higgins, B; Shute, J K
Abstract : Background: There is evidence of activation of the extrinsic coagulation cascade in the asthmatic airway, and both plasma and locally derived factors may be involved. The hypothesis that the normal haemostatic balance of healthy airways sampled by sputum induction favours fibrin formation in asthmatic airways, and that inhaled corticosteroids (ICS) and plasma exudation influence this balance, was tested. Methods: ELISA and activity assays were used to measure α2 -macroglobulin (an index of plasma leakage) and coagulation factors in hypertonic saline-induced sputum of 30 stable subjects (10 controls, 10 with moderate asthma and 10 with severe asthma). Additionally, the moderate cohort were weaned off their ICS, followed by further sputum induction 5 days after cessation of steroids. Results: ICS wean induced a significant rise in plasminogen (median (interquartile range (IQR)): 13.92 (6.12–16.17) vs 4.82 (2.14–13.32) ng/ml; 95% CI 0.003 to 8.596, p = 0.0499) and tissue plasminogen activator (tPA; 5.57 (3.57–14.35) vs 3.88 (1.74–4.05) ng/ml; 95% CI 0.828 to 9.972, p = 0.0261) levels in sputum, such that tPA in untreated moderate asthma was significantly (p = 0.0029) higher than normal (2.14 (0.0–2.53) ng/ml). Subjects with severe asthma had significantly more α2 -macroglobulin (p = 0.0003), tissue factor (p = 0.023), plasminogen activator inhibitor (p = 0.0091), thrombin-activatable fibrinolysis inhibitor (p = 0.0031) and fibrin degradation products (p = 0.0293) in their sputum than control subjects. Conclusion: Untreated moderate asthma is associated with increased fibrinolysis that is corrected by ICS. Severe asthma and high dose corticosteroid therapy is associated with a profibrinogenic, antifibrinolytic environment in the airways. This study suggests that inhibition of fibrin deposition in severe asthma may be a therapeutic approach.